PERSAINGAN PERBANKAN BERDASARKAN JENIS BANK DI INDONESIA - Nur Fatwa (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study employs census samples of 106 conventional banks actively operating activities of banking business in Indonesia. In this research use sample size 72 based on bank type. The method implemented in this study is a quantitative approach by applying secondary data taken from Monetary Authority and Financial Services Authority. In order to discover the banking industry competition in Indonesia. The data analysis in this study uses pool data which combine time series and cross sectional known as panel data. The result of the research shows that the market share of deposit of state-owned banks, private national banks of foreign exchange, national private non-foreign exchange banks, regional development banks, mixed banks, foreign banks have a significant positive effect on return on assets. The results of the tests show that market share of loan of state-owned banks, national private foreign exchange banks, national private non-foreign exchange banks, regional development banks, mixed banks, foreign banks have no effect on return on assets.